2020
DOI: 10.32734/ijnpc.v2i01.3503
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of TNF-Α Expression to Clinical Stadium in Nasopharyngeal Carcinoma

Abstract: Introduction: Nasopharyngeal carcinoma (NPC) is one of the most common malignancies in Indonesia with over 13.000 new cases reported yearly, especially in the male. The TNF-α serum is reported as a new biomarker to predict bone invasion, post-therapy distant metastasis, and poor life sustainability in NPC. Objective: To identify the expression of TNF-α in regards to the clinical stage of NPC. Material and methods: This is an analytic study with 126 NPC samples of patients in Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…46 Susilo et al also reported a significant association between TNF-α protein expression and advanced-stage NPC. 28 In addition, as reported by Akinmoladun et al, no significant difference was found in the serum levels of TNF-α in patients with head and neck cancers, such as NPC, compared with the normal group, which is consistent with our findings. 47 It is noted that mRNA was extracted from FFPE specimens in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…46 Susilo et al also reported a significant association between TNF-α protein expression and advanced-stage NPC. 28 In addition, as reported by Akinmoladun et al, no significant difference was found in the serum levels of TNF-α in patients with head and neck cancers, such as NPC, compared with the normal group, which is consistent with our findings. 47 It is noted that mRNA was extracted from FFPE specimens in the present study.…”
Section: Discussionsupporting
confidence: 93%
“… 26 Also, several studies have considered serum TNF-α as a novel prognostic biomarker to predict bone invasion and posttreatment distant metastasis in NPC patients. 27 28 …”
Section: Introductionmentioning
confidence: 99%